HUBUNGAN UMUR IBU DAN LAMA PERSALINAN DENGAN KEJADIAN RUPTUR PERINEUM PADA IBU PRIMIPARA DI BPS NY. IDA FARIDA DESA PANCASAN KECAMATAN AJIBARANG KABUPATEN BANYUMAS TAHUN 2010 - Mustika, Saras Ayu; Suryani, Evi Sri (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2011)
Rupture perineumÂ is theÂ woundÂ of the perineumÂ causedÂ by tissueÂ damageÂ due toÂ naturalÂ pressureÂ of the fetal headÂ orÂ shoulder during delivery.Â rupture perineum is the one of cause by lowering womanâ€™s quality of life that influenced to womanâ€™s reproductive organ. Mother age andÂ  deliveryâ€™s duration usually can cause rupture perineum.Â The incidence ofÂ rupture perineumÂ inÂ BPSÂ IdaÂ Farida atÂ Â Pancasan VillageÂ AjibarangÂ Subdistrict Banyumas Regency 2010 aroundÂ 89 peopleÂ (67.4%)Â of the totalÂ laborÂ 132 peopleÂ in 2010. To know the relationship of mother age and deliveryâ€™s duration to primipara mother with rupture perineum insidence at BPS Ida Farida at Pancatan Village Ajibarang Subdistrict Banyumas Regency in 2010. The researcher used a case control with retrospective approach. The data analysis used univariate analysis with used statistics descriptive and bivariate analysis with used chi square test. The population at this research was the primipara delivery mother at BPS Ida Farida at Pancatan Village Ajibarang Subdistrict Banyumas Regency in 2010 with 20Â  cases samples and 20 control samples used purposive sampling technique. Respondents who reproductive age (20-35 years old) around 25 respondents (62,5%) andÂ  normal deliveryâ€™s duration around 31 respondents (77,5%). There was relationship between mother age with rupture perineum with Ï value 0,022 < Î± 0,05 and there was relationship delivery duration with rupture perineum with Ï value 0,020 < Î± 0,05. There was relationship between mother age and delivery duration with rupture perineum. For health worker should always provide counseling and give information to pregnant woman espescially primigravida about motherâ€™s condition that can cause rupture perineum and delivery characteristics in order to minim rupture perineum insidense. Keywords: mother age and deliveryâ€™s duration, rupture perineum